Low-bandgap conjugated polymers based on alkylthiothienyl-substituted benzodithiophene for efficient bulk heterojunction polymer solar cells. (28th July 2017) - Wang, Xunchang; Tong, Jinhui; Guo, Pengzhi; Li, Yuda; Li, Hui; Xia, Yangjun; Wang, Feng
Abstract: Three two-dimensional (2D) conjugated polymers, named PBDTSDPP-1, PBDTSDPP-2, and PBDTSDPP-3, based on benzo[1, 2-b:4, 5-b']dithiophene (BDT) donor unit with conjugated alkylthiothiophene side chain and diketopyrrolopyrrole (DPP) acceptor unit, were designed and synthesized via palladium-catalyzed Stille-coupling reaction. The resulting polymers exhibited good thermal stability with a high decomposition temperature over 350 °C and a broad absorption in the range from 400 to 900 nm. The HOMO energy levels of the polymers are deeper than −5.39 eV and the LUMO energy levels of them are higher than −4.09 eV. The field effect transistors prepared from PBDTSDPP-1, PBDTSDPP-2 and PBDTSDPP-3 provide a hole mobility of 3.52 × 10 −3, 3.85 × 10 −4 and 4.36 × 10 −3  cm 2  V −1  s −1, respectively. The photovoltaic properties of the polymer as donor was investigated with an inverted structure of ITO/PEIE/polymer:PC71 BM/MoO3 /Ag. As a preliminary result, PBDTSDPP-1, PBDTSDPP-2, and PBDTSDPP-3 showed power conversion efficiency (PCE) of 4.75%, 3.56%, and 5.28%, respectively. The short-circuit current density ( J SC ) and PCE value of PSCs based on PBDTSDPP-3 are higher than those of the other two polymers because of better morphology, higher and more balanced charge-carrier mobilities, leading to less recombination loss. Graphical abstract: Highlights: BDT with alkylthiothiophene side chain was polymerized with DPP to obtain π-conjugated polymers. The effect of side chain length on the photovoltaic properties of polymers is investigated. The optimal device performance reached a power conversion efficiency of 5.28%.